Evaluating Medical College Lib Guides: A Usability Case Study - Ghulam Farid, Sadia Zaheer, Ayesha Khalid, Alia Arshad, Muhammad Kamran (Pakistan Journal of Medical & Health Sciences, 2022)
Many libraries have adopted usability testing as a standard practise for ensuring that their online presence is user-friendly and accessible. This study attempt to test usability of LibGuides platform at Shalamar Teaching Hospital, Lahore. The purpose of this qualitative research is to examine the usability, user experience (UX), and information architecture (IA) of LibGuides in the institutional context of Shalamar Medical & Dental College, Lahore, The research explored users’ views and was then extended to discuss the general utility of the Shalamar LibGuides. In this aspect, the study is remarkable because there is a paucity of literature on the subject. Keywords: user-centered design, subject guides, LibGuides, Pakistan, usability; research guides; Medical libraries